A systematic review of the concept of self-regulation in infants between 0 and 36 months in Latin America - Santos, Jorge Alejandro; Giovannetti, Federico; Smulski, Mariana Celeste; Hermida, María Julia; Petetta, Daniel Roberto; Segretin, María Soledad; Lipina, Sebastián Javier (Elsevier, 2024)
This paper aims to identify how cognitive and emotional self-regulation (SR) processes in infants from 0 to 36 months are defined within the Latin American academic context. A systematic review based on the PRISMA methodology was implemented to review the conceptual and operational definition of SR, the type of study, the country of origin of the authors, and the reference to the adequacy of the research to the specific cultural context of Latin America. Twenty-two papers that met the selection criteria were selected. The study identified four types of conceptual definitions for SR, each associated with different constructs or sets of constructs: executive functions, temperament, the integration of executive functions and temperament, and physiological homeostasis. These definitions were based on mainstream approaches to SR rather than being specific to the Latin American region. The study also found compatibility between the sample and some observed trends. On one hand, there was an underrepresentation of the Latin American population in high-impact publications on the subject. However, from 2010 to the present, there is evidence of growth in publications on SR in the analyzed sample. On the other hand, the sample also indicates a disparate representation of the countries of Latin America and the Caribbean in existing publications. Finally, concerning the adaptation to the cultural context of the research, a small number of studies addressed this variable in a specific and significant way. However, even in these cases, the approach is based on models and hypotheses that are limited to understanding the Latin American region’s cultural, socioeconomic, and demographic diversity.
Keywords: Ciencias sociales::Ciencias de la educación::Educación, general (incluyendo entrenamiento, pedagogía, didáctica)